Food Suplement Controlling Pada Balai Besar Pengawas Obat Dan Makanan (BPOM) Pekanbaru - Nurpeni; Widia Astuti; Abdul Mirad; Aguswan; Trio Saputra (Universitas Lancang Kuning, 2022)
This service aims to analyze food supplement controlling by the Pekanbaru Food and Drug Supervisory Center with a focus on food supplement supervision. The data analysis method is carried out with a qualitative approach by formulating the existing problems by providing a thorough understanding and analysis by comparing the data that has been obtained in the field. Supervision of food supplement products by Balai Besar POM Pekanbaru is carried out by preparing standards and requirements for product quality and production and distribution by taking into account all aspects of production and quality control, covering the entire series of making food supplements with the aim of ensuring that the products produced always meet quality requirements. which has been determined in accordance with the purpose of its use